PENYIDIKAN POLRI DALAM SISTEM PERADILAN PIDANA DI INDONESIA (STUDI PENELITIAN POLRES KENDAL) - Ahmad Masdar Tohari; Jawade Hafidz (UNISSULA Semarang, 2017)
The Criminal Justice System as a system in criminal law enforcement seeks to address crime issues is interpreted as an attempt to control or limit crime to be within the limits of public tolerance. Issues raised in this study include: 1) what are the obstacles faced by Police investigators in the implementation of the investigation related to the criminal justice system and how to deal with these barriers ?; 2) how is the criminal justice system investigation policy that should be implemented?The approach method used in this research is normative juridical approach method.The results of this research are: 1) obstacles faced by Police investigators in criminal investigation process are: a) lack of witness participation in giving information in process of investigation; b) there are still many investigators whose education level is still low; c) limited number of investigators; d) inadequate income / salary factor of the investigator; e) lack of budget for investigation; f) inadequate facilities and infrastructure to support investigator performance. The way to overcome the obstacles faced by Polri investigators in the implementation of the investigation related to the criminal justice system in the police station is: a) the need to make the law on duty and authority; b) the need for presence or willingness to bear witness to what is seen, experienced, and known; 2) the investigation is regulated in the Draft of Criminal Procedure Code II of Investigator and Investigation and Chapter IV Arrest, Detention, Body Search, House Income, Foreclosure and Letters Inspection. The investigation process of Police as regulated by Draft of Criminal Procedure Code is as follows: a) arrest; b) searches; c) detention; d) eavesdropping. Keywords: Investigation, Investigator, Police, Criminal Justice System